Extracellular vesicles derived from the feces of pregnant women modulate T cells toward a pregnancy-supportive phenotype in vitro - Dietz-Ziegler, Stefanie; Kewitz, Samantha; Kaiser, Gabriele; Rühle, Jessica; Marmé, Alexander; Dalpke, Alexander; Cheaib, Bachar; Pauluschke-Fröhlich, Jan; Henes, Melanie; Velic, Ana; Pich, Andreas; Vollert, Anneli; et al. (European journal of immunology, 2025)
Pregnancy requires immune tolerance to a semi-allogeneic fetus, involving profound adaptations, particularly in the T helper (Th) cell response. The intestinal microbiome plays a crucial role in health, but its influence on immune adaptation to pregnancy remains unclear. Bacterial extracellular vesicles (BEVs), released by gut bacteria, can cross the intestinal barrier and modulate immune responses. In our study we investigated the effect of fecal EVs (fEVs) from pregnant women on Th cell composition in vitro. fEVs were purified from preserved stool samples, characterized, and their uptake by immune cells was analyzed. Using an in vitro T cell culture model, we examined Th cell phenotypes, intracellular cytokine expression, and proteomic changes after stimulation with fEVs from pregnant and non-pregnant women. We demonstrate that fEVs from preserved stool samples are rapidly taken up by T cells and modulate their phenotype. Stimulation with fEVs from pregnant women shifts Th cells toward a regulatory profile favorable for pregnancy, increasing Th2 cells while reducing Th17 cells compared to fEVs from non-pregnant controls. This study provides the first in vitro evidence that fecal-derived EVs influence immune adaptation to pregnancy and may offer a basis for microbiome-targeted strategies to prevent or treat immunological pregnancy complications.
Gesehen am 12.02.2026